Design guidelines for dynamic mathematics worksheets - Hohenwarter, Markus; Preiner, Judtih (Teaching Mathematics and Computer Science, 2008)
In a Math and Science Partnership project in Florida, middle school teachers are using the dynamic mathematics software GeoGebra to create interactive online worksheets for mathematics learning. Formative evaluation of these materials based on design principles of multimedia learning has lead to a list of specific design guidelines for such dynamic worksheets that we present in this article. These design guidelines can give advice both for the creation of new dynamic worksheets and the evaluation of existing material on the Internet.